Pelatihan Pemanfaatan Sisa Nasi Menjadi Krupuk Sebagai Upaya Pengurangan Limbah Makanan Rumah Tangga - Sifa', Moh. Agus; Novitasari, Nurul; Nikmah, Aliyatun; Muctharom, Moch. Zaenal Azis (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Household food waste, especially leftover rice, is an environmental issue that is often overlooked but has significant impacts. Sumengko Village, located in Kalitidu District, Bojonegoro Regency, is an area with high household activity, resulting in a considerable amount of rice waste generated daily. This community service program aimed to provide training for local residents on how to utilize leftover rice by transforming it into a value-added product: rice crackers. The methods used in this activity included socialization, demonstrations of rice cracker production, and hands-on practice with participants. The results showed that the training successfully increased the participants’ knowledge and skills in processing rice waste into a marketable food product. In addition to reducing the volume of food waste, this program also opened opportunities for sustainable home-based businesses. Therefore, this training made a positive contribution both to environmental preservation and to the economic empowerment of the village community.